Essays on the Industrial Organization of Transport, Retail and Health Markets - Schäfer, Jan Thomas; Justus Liebig University Giessen (My University, 2024)
This doctoral thesis, Essays on the Industrial Organization of Transport, Retail, and Health Markets, investigates how regulatory changes, market structures, and government intervention shape outcomes in these sectors. The manuscripts examine topics including the regulation of Rx rebates in health markets, the strategic use of extended shopping hours in grocery retail, entry deterrence in transport markets, and the financial frameworks of European railways. Despite their diverse contexts, the manuscripts share a focus on analyzing the effects of regulatory changes and market adjustments within the framework of industrial organization. They employ similar methodological approaches, using variation across entities - such as states or regions - or exploiting (natural) experiments to identify causal effects. Most manuscripts rely on panel data and apply methods such as Data Envelopment Analysis (DEA), Fixed-Effects Models, Difference-in-Differences (DID), and Instrumental Variable techniques.
Keywords: ddc:330